dCas9-HDAC8-EGFP fusion enables epigenetic editing of breast cancer cells by H3K9 deacetylation - Mohammad Mijanur Rahman; Trygve O. Tollefsbol (European Journal of Cell Biology)
Epigenetic editing is thriving as a robust tool for manipulating transcriptional regulation and cell fate. Despite its regulatory role in gene downregulation, epigenetic editing with histone deacetylation has been sparsely studied, especially in the context of cancer. In this current study, we have reconstructed a dCas9-HDAC8-EGFP fusion to perform histone deacetylation on the promoter of the ESR1, TERT and CDKN1C genes for the first time in breast cancer cell lines MCF-7 and MDA-MB-231 as well as in HEK293T cells. Our results demonstrated that dCas9-HDAC8-EGFP in combination with appropriate gRNAs were able to downregulate the expression of the ESR1, TERT and CDKN1C genes transcriptionally by specifically depleting the H3K9ac level on the recruitment loci. The addition of histone deacetylase inhibitors was found to neutralize the outcomes of dCas9-HDAC8-EGFP-induced epigenetic editing. Furthermore, we observed a significant downregulation of full length ERα expression in epigenetically edited MCF-7 cells with consequential alteration in cellular response toward estradiol and tamoxifen treatment due to dCas9-HDAC8-EGFP mediated epigenetic editing of the ESR1 gene. Overall, dCas9-HDAC8-EGFP is a novel circuit that enabled downregulation of crucial genes with cellular outcome in breast cancer cells by preferentially inducing H3K9 deacetylation of specific promoter regions.